Obesity as a risk factor for COVID-19 breakthrough infection among the fully vaccinated urban population of South Gujarat – A retrospective cohort study - Mayank Jha; Pratham Kholwadwala; Vatsal Kalariya; Mamta Rani; Jayant Patel; Hitesh Shah; Rushikesh Shukla (Journal of Family Medicine and Primary Care)
Background and Objectives: There is more possibility of COVID-19 among obese people; hence, research into how well vaccinations work in this population should be focused. More scientific studies are required to document the effect of body mass index (BMI) on the usefulness of the adenovirus vector vaccine as reviews are lacking. This study was done to see the association between obesity with COVID-19 infections due to poor vaccine response among them. Methods: A cohort of fully vaccinated individuals of a city in western India were contacted, and a retrospective cohort study was conducted. An average of 400–425 participants among the obese group (exposed) and an average of 400–425 participants among the nonobese group were taken. Data on sociodemographic details, vaccination status, height and weight for BMI calculation, COVID-19 infection status, and its clinical features were collected using predesign, pretested, semistructured questionnaires. Societies were randomly selected from eight different zones of the city, and all the eligible individuals of the society available at the time of survey were interviewed. Data entry and analysis were done using Microsoft excel, Open Epi, Quantpsy, and SPSS-16 software. Relative risk and odds ratios were calculated in open epi software. Results: The ratio of obese to nonobese individuals was 1:1. Accordingly, 409 obese and 409 nonobese participants were recruited. The mean age of participants was 41.3 ± 14.9 years. As high as 144 (17.6%) of respondents were having history of previous infection before vaccination, and around 42 (5.1%) respondents of the overall study population were infected after the first dose of vaccination. The total count of people for infections before receiving a single dose of vaccination irrespective of body status was reported to be 144 (17.6%) out of a total of 818 candidates. Interpretation and Conclusions: We can conclude that not only obesity is a risk factor but also it increases the severity of COVID-19 infection.